GAGASAN STUDI AGAMA TERAPAN DALAM BINGKAI KAMPUS MERDEKA: PERSPSEKTIF SOSIOLOGI PENGETAHUAN - Ahmad Muttaqin; Ustadi Hamsah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
One of the big questions frequently asked by Senior High School Students who were interested in studying Religious Studies is about the career opportunity of the department’s alumni. Unlike other applied sciences that have a clear path of the alumni’s career, religious studies seem to vague in providing jobs for its alumni due to its pure/basic science characteristic. This paper proposes the possibility to develop applied religious studies to answer such a question. The author traces characteristics of religious studies from a sociology of knowledge perspective and then proposes eight fields of applied religious studies, which from a sociological perspective, meets the need for the implementation of “Freedom to Learn, Independent Campus” (Merdeka Belajar- Kampus Merdeka, MBKM), a policy from Ministry of Education and Culture, the Republic of Indonesia.